2003
DOI: 10.1063/1.1570319
|View full text |Cite
|
Sign up to set email alerts
|

Sensor Technology for Integrated Vehicle Health Management of Aerospace Vehicles

Abstract: ABSTRACT. NASA is focusing considerable efforts on technology development for Integrated Vehicle Health Management systems. The research in this area is targeted toward increasing aerospace vehicle safety and reliability, while reducing vehicle operating and maintenance costs. Onboard, real-time sensing technologies that can provide detailed information on structural integrity are central to such a health management system. This paper describes a number of sensor technologies currently under development for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…These high-value assets include but not limited to, civil and military aircraft [2], wind turbines which make a significant contribution towards renewable energy generation [3], and metal or plastic-lined composite pressure vessels that are used as fuel tanks for space vehicles and other applications [4,5]. However, composite structures do have weaknesses which is highly susceptible to damage from accidental impacts [1,[6][7][8][9][10]. Multiple studies have been conducted and found that even relatively low-energy impacts that leave little to no visual evidence of damage can cause substantial reductions of up to 60% in compressive strength [7,8], which presents an unacceptable risk of failure for such high-value or safety critical structures.…”
Section: Quantitative Characterisation Of Acoustic Emission Source Fo...mentioning
confidence: 99%
“…These high-value assets include but not limited to, civil and military aircraft [2], wind turbines which make a significant contribution towards renewable energy generation [3], and metal or plastic-lined composite pressure vessels that are used as fuel tanks for space vehicles and other applications [4,5]. However, composite structures do have weaknesses which is highly susceptible to damage from accidental impacts [1,[6][7][8][9][10]. Multiple studies have been conducted and found that even relatively low-energy impacts that leave little to no visual evidence of damage can cause substantial reductions of up to 60% in compressive strength [7,8], which presents an unacceptable risk of failure for such high-value or safety critical structures.…”
Section: Quantitative Characterisation Of Acoustic Emission Source Fo...mentioning
confidence: 99%
“…The IVHM software will never directly command any vehicle subsystems and under no circumstances would its recommendations be acted upon automatically by the vehicle. The VMS then telemeters this information to the ground, where ground software processes and displays the information [15][16][17].…”
Section: The Present Research Situation Of Health Management Formentioning
confidence: 99%
“…Although sensor suites tend to be specific to the application domain, a few developmental sensor technologies are taking central stage in the IVHM domain. These include micro and fibre optic technologies that reduce sensor size, weight, and support requirements [19,42] together with increasingly advanced smart sensors that have Fig. 2 Architecture of an IVHM system opened up the possibility for widespread introduction of embedded sensor systems [13].…”
Section: Technology Principles For Ivhm Systemsmentioning
confidence: 99%